Working Towards a Proficiency Scale of Business English Writing: A Mixed-Methods Approach - Wang, Li; Fan, Jason (Springer Nature Singapore : Imprint: Springer, 2021)
XIV, 175 p. 13 illus., 3 illus. in color.